Optimasi Kapasitas Produksi Assembly Line LED Downlight PT. DEF - Ririn Desfiasri Desfiasr; Andira Andira (JIE Scientific Journal on Research and Application of Industrial System, 2016)
PT. DEF is a manufacturing company that produces lighting fixture. Light Emitting Diode (LED) down-light is one of the company flagship products. With the new type (LGB72316 LE1 and LGB72317 LE1) and the company's policy not to add man-power in production units lead automatically in addition of work hours on the production schedule that’s resulting in increased overtime. After a series of data collection and testing, as well as the determination of standard time on the assembly line work related, research shows that low line efficiency (66.55%) and the balance delay is high (33.45%). This is an indication of poor performance related on the assembly line. Line balancing would be an alternative problem solving tools to overcome these problems. This study tried to draft a new balancing method Helgeson-Birnei, Moodie Young and Kilbridge-Wester Heuristics. Of a series of procedures that have been performed, the method Kilbridge-Wester Heuristics showed the best results. The method is able to improve performance by reducing cycle time, product of 35.17 seconds / products became 32.88 seconds / products and generate 6 work stations with 6 operators, line efficiency 94.91%, balance delay 5.09%, smoothness index of 6,224 and labor cost saving of Rp 7,215,011.27 per month.